The Design And Simulation Of Flow Mode Electrorheological Damper - Mukhlis, Reiza Zakia; Nik Mohamed2, Nik Abdullah; Mohd. Nor, Mohd. Jailani (Penerbit UTM Press, 2006)

(untitled)
Electrorheological (ER) Damper Is A Damper That Utilizes Electrorheological Fluid As The Working Fluid. By Changing The Strength Of Applied Electric Field To The Fluid, The Flow Resistance Of The Fluid Changes And Hence The Damping Characteristic Could Be Adjusted. This Paper Provides Theoretical Formulation To Calculate The Damping Constant Of Semi-Active Flow Mode ER Damper. The Formula Is Developed By Analyzing Fluid Velocity Profile That Flows In Electrode Gap. From The Simulation, It Shows That Electric Field Strength Gives Severe Effect To The Damping Level Of The Damper. Without Applying Electric Field, A Reduction On The Gap Of Electrode From 3 To 1 Mm Will Increase The Damping Constant Value By A Factor Of Only 27, While With A 3 Kvmm–1 Electric Field Being Applied, The Increase Is By A Factor Of 595.